Eksplorasi Dampak Media Online Terhadap Keterlibatan Mahasiswa Pendidikan Teknik Bangunan Pada Kelompok Mata Kuliah Yang Berbeda - Permatalestari, Indah; Iriani, Tuti; Ramadhan, Muhammad Agphin (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2024)
In an increasingly digital era, the use of online media in learning is considered very important. This research aims to determine the impact of using online media by students in the Education and Structure subject group in the UNJ Building Engineering Education study program. This research is quantitative research with a survey method. The population of this study were students from the 2017 and 2018 Building Engineering Education study programs who had carried out structure and education courses in the even semester (112) of the 2019/2020 academic year, totaling 297 students. The sampling technique in this research used cluster random sampling, so the sample consisted of 160 students. Data collection uses a questionnaire. The research results show that education courses use online media more than structured courses. Apart from that, the most widely used online media are Google Classroom and Whatsapp groups, with a percentage of more than 80%. The types of online media used in the Education course group include Google Classroom, Whatsapp group, email, and Quizzizz. Meanwhile, the online media structure course group only uses Google Classroom and Whatsapp groups. Students use online media to get references or learning resources, as a means of discussion, download study materials, and make it easy for students to access online media in the excellent category.